Retro‐1 Analogues Differentially Affect Oligonucleotide Delivery and Toxin Trafficking. (25th October 2016) - Yang, Bing; Ming, Xin; Abdelkafi, Hajer; Pons, Valerie; Michau, Aurelien; Gillet, Daniel; Cintrat, Jean‐Christophe; Barbier, Julien; Juliano, Rudy
Abstract: Retro‐1 is a small molecule that displays two important biological activities: First, it blocks the actions of certain toxins by altering their intracellular trafficking. Second, it enhances the activity of oligonucleotides by releasing them from entrapment in endosomes. This raises the question of whether the two actions involve the same cellular target. Herein we report the effects of several Retro‐1 analogues on both toxins and oligonucleotides. We found analogues that affect toxins but not oligonucleotides and vice‐versa, while Retro‐1 is the only compound that affects both. This indicates that the molecular target(s) involved in the two processes are distinct. Abstract : Clarity in Retro‐spect : Both oligonucleotides (red ribbons) and toxins (orange squares) enter cells by endocytosis and traffic to early endosomes (EE). Oligos traffic to late endosomes (LE) and thence to lysosomes (LY), where they are degraded. Toxins traffic via the Retromer complex (R) to the trans Golgi (TG) to become active. Retro‐1 blocks toxin trafficking and also releases oligos from late endosomes.